Factors Associated With Patient-Initiated Telephone Calls After Orthopaedic Trauma Surgery. Issue 3 (March 2017) - Hadeed, Michael M.; Kandil, Abdurrahman; Patel, Vandan; Morrison, Avery; Novicoff, Wendy M.; Yarboro, Seth R.
Abstract : Objectives: The primary aim of this study is to investigate the incidence of early patient-initiated postoperative telephone calls and reasons for those calls. Secondary goals are to determine perioperative predictive factors for calls including the procedures most frequently associated with them. Design: Retrospective chart review. Setting: Academic Level-1 Trauma Center. Patients/Participants: Six hundred eighty-four patients who underwent surgical treatment by our orthopaedic trauma division between 01/01/2014 and 31/12/2014. Main Outcome Measurements: Patient-initiated telephone call documented within 14 days after discharge. Results: Twenty-nine percent (n = 199) of patients initiated a telephone call within 14 days after discharge. The most common reasons for telephone calls were pain control (22%), bathing/dressing/wound questions (16%), and questions regarding discharge medications (8%). The procedures associated with the highest percentage of telephone calls were tibial shaft intramedullary nailing (36.0%), calcaneus open reduction internal fixation (31.3%), and cephalomedullary nailing for proximal femur fractures (29.3%). Perioperative factors predictive of an increase in phone calls included discharge directly to home, higher baseline level of health of the patient (based on comorbidities and the American Society for Anesthesiologists score), and a more robust support network (based on marital and employment status). Conclusions: This study identifies the incidence and common reasons for patient-initiated calls after orthopaedic trauma surgery and an analysis of perioperative factors predictive of increased phone calls. These data give direction for communication at the time of discharge to improve efficiency, patient care, and patient satisfaction. Level of Evidence: Prognostic Level IV. See Instructions for Authors for a complete description of levels of evidence.